Leading for instructional improvement : how successful leaders develop teaching and learning expertise - Fink, Stephen L.; Markolt, Anneke (Hoboken, NJ : Jossey-Bass, 2011)
'There is little agreement among school leaders on what constitutes quality teaching and how best to support teachers in improving lessons, assessments, and classroom instruction. This book will show how principals and other school leaders can'grow' the expertise of teachers to deliver high quality instruction that serves all students well. It introduces principals to a five-part model of effective instruction. It then shows leaders how to make use of this framework for guiding new and veteran teachers on improving lessons, instruction, and other aspects of classroom practices.'--
Includes bibliographical references (p. 257-261) and index.
Keywords: Educational leadership -- United States; School administrators -- United States; School management and organization -- United States; Teacher effectiveness -- United States; Effective teaching -- United States; Educational change -- United States; EDUCATION / General